Pengaruh Bawang Merah (Allium Cepa, L.) Terhadap Penurunan Kadar Kolesterol Darah Pada Penderita Hiperlipidemia Di Wilayah Kerja Puskesmas Karangnongko Kabupaten Klaten - Agus Winarso; Youstiana Dwi Rusita; Bambang Yunianto (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Cholesterol Blood, Red Onion (Allium Cepa, L.), Hyperlipidemia. Changes in lifestyle, diet, and advances in technology may lead to a decline in physical activity in the community, resulting in the occurrence of energy imbalance. Hyperlipidemia was a condition to an increase in cholesterol and or triglyceride serum upper limit of normal. Onion (Allium cepa, L) contains quercetin in high enough levels can reduce total cholesterol. This study used a sample of onion powder capsules that aims to determine the effect of onion (Allium cepa, L.) to decrease blood cholesterol levels in patients with hyperlipidemia. This research is a pre-experimental design, wherein the treatment group was given capsules of onion (Allium cepa, L.) using a randomized experimental design pretest-Post test Group Design. This study uses the Shapiro Wilk normality test with the sample amounted to 31 people. Based on the results of non-parametric Wilcoxon statistical test showed that cholesterol levels before taking capsules red onion ranged between 226 mg/dl and 370 mg/dl with an average of 281.7 mg/dl. While cholesterol levels after consuming capsules onion ranged between 129 mg/dl and 400 mg/dl with an average of 273.7 mg/dl. The value of p = 0.737 (α ˃ 0.05) means that there is not a statistically significant effect capsule onion powder to decrease cholesterol levels.